I DOCENTI DI ITALIANO A STUDENTI SINOFONI AFFERENTI AI PROGRAMMI MARCO POLO E TURANDOT FRA ITALIA E CINA (Italiano LinguaDue, 2021)
Il presente articolo presenta un lavoro di ricerca sui teachers’ beliefs specificatamente dedicato ai docenti di lingua e cultura italiane ad apprendenti sinofoni afferenti ai Programmi governativi Marco Polo e Turandot. I docenti intervistati non provengono dallo stesso contesto lavorativo: alcuni di essi lavorano per istituzioni di tipo privato, altri di tipo pubblico. Inoltre alcuni operano in Cina, altri in Italia; alcuni sono di nazionalità cinese, altri italiana. Proprio la provenienza eterogenea per nazionalità e contesti operativi rende lo studio un interessante specchio della situazione attuale dell’insegnamento dell’italiano a studenti cinesi a livello accademico. Teachers of Italian for synophone students in the Marco Polo and Turandot Programs between Italy and ChinaThis article presents a research project on teachers' beliefs specifically dedicated to teachers of Italian language and culture to Sino-speaking learners belonging to the governmental programs Marco Polo and Turandot. The teachers interviewed do not come from the same working context: some of them work for private institutions, others for public ones. Moreover, some work in China, others in Italy; some are of Chinese nationality, others Italian. It is precisely this heterogeneous origin in terms of nationality and operating contexts that makes the study an interesting mirror of the current situation of teaching Italian to Chinese students at the academic level.